(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
In this paper, we describe a case study conducted with graduate students in a major diverse university and suggest the addition of a more contemporary facet to the Openness to Diversity and Challenge (ODC) scale created by Pascarella and colleagues in 1996 which rests on sharing and symmetry. The intriguing behavior of students relating an assignment about multiculturalism, led us to review and update the ODC scale by integrating a self-oriented symmetric side to the scale previously based exclusively on others-oriented measure. Our research was composed of two phases. The first one was based on a case study using the direct-observation approach as the data collection method. The second one was testing the symmetric ODC scale through a 5-point Likert scale on a sample of 56 graduate business students in order to identify the relevance of the suggested update of the 25 year-old ODC scale. Results demonstrated that the main factor intervening in the use of scales remains the Social Desirability Bias (SDB) what comforted us in the accuracy of the direct observation method as an appropriate approach to study Openness to Diversity. Our findings also confirmed that the widespread use of the ODC scale created in 1996 does not reflect the contemporary young mindsets and reality.